2021
DOI: 10.1186/s13068-021-01879-0
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the roles of the reductant and free copper ions in LPMO kinetics

Abstract: Background Lytic polysaccharide monooxygenases (LPMOs) are monocopper enzymes that catalyze oxidative depolymerization of industrially relevant crystalline polysaccharides, such as cellulose, in a reaction that depends on an electron donor and O2 or H2O2. While it is well known that LPMOs can utilize a wide variety of electron donors, the variation in reported efficiencies of various LPMO-reductant combinations remains largely unexplained. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 79 publications
(138 citation statements)
references
References 56 publications
3
125
2
3
Order By: Relevance
“…This shows that indeed LPMO is limiting the apparent monooxygenase reaction, which is in contrast to observations made for other LPMOs whose reactions may be limited by H 2 O 2 -generating LPMO-independent side reactions involving the reductant and O 2 . 53 Importantly, the rate at the intercept (0 μM LPMO) was significant (0.0184 μM*s –1 ). Of note, this “LPMO-independent” background level of substrate conversion is effectively inhibited by HRP ( Figure 3 A,B), which shows that this conversion involves H 2 O 2 generated in solution, likely resulting from auto-oxidation of ascorbic acid 53 and is not due to, for example, a true monooxygenase reaction that would not involve H 2 O 2 .…”
Section: Resultsmentioning
confidence: 92%
“…This shows that indeed LPMO is limiting the apparent monooxygenase reaction, which is in contrast to observations made for other LPMOs whose reactions may be limited by H 2 O 2 -generating LPMO-independent side reactions involving the reductant and O 2 . 53 Importantly, the rate at the intercept (0 μM LPMO) was significant (0.0184 μM*s –1 ). Of note, this “LPMO-independent” background level of substrate conversion is effectively inhibited by HRP ( Figure 3 A,B), which shows that this conversion involves H 2 O 2 generated in solution, likely resulting from auto-oxidation of ascorbic acid 53 and is not due to, for example, a true monooxygenase reaction that would not involve H 2 O 2 .…”
Section: Resultsmentioning
confidence: 92%
“…2b). (Stepnov et al, 2021). Furthermore, molecular dynamic simulations using the quantum mechanics/molecular mechanics (QM/MM) method have demonstrated that ascorbate rapidly reduces LPMO-Cu(II) in a thermodynamically favorable process (Wang et al, 2019;Wang et al, 2020).…”
Section: Substrate Specificity and Electron Donor Preferencementioning
confidence: 99%
“…Another aspect to consider when using this assay is the amount of H 2 O 2 generated by the reaction of the reductant with oxygen. Stepnov et al compared the effects of different amounts of gallic or ascorbic acid, highlighting the striking effect that free copper in LPMO preparations can have on the determination of LPMO rates [78]. with the Amplex TM Red assay before (green and blue lines) and after (brown and red lines) enzyme purification.…”
Section: Amplextm Red/horseradish Peroxidasementioning
confidence: 99%